Rotavirus Diarrhoea among Children under Five Years in a Tertiary Level Government of Rajasthan - Ari, Abhijit; Chaudhary, Ruchi; Sharma, S.D. (Journal of Nepal Paediatric Society, 2017)
Introduction: Rotavirus is the leading cause of severe, dehydrating diarrhoea in young children globally. Studies indicate that rotavirus causes approximately 40 percent of childhood diarrhoea hospitalization worldwide and around 39 percent in India in less than 5 years of age. This study aimed to estimate the prevalence of rotavirus diarrhea among hospitalized children aged under five years. Materials and Method: Stool samples were collected from children who fall within the age range of 0-5 years with acute diarrhea and samples are tested for rotavirus by the enzyme linked immunosorbent assay (ELISA). Result: Out of 349 samples, 104(29.8%) cases were positive for rotavirus by ELISA. Therefore the prevalence of rotavirus infection among hospitalized patient under this study was 29.8%. Conclusion: Rotavirus is an important cause of diarrhea in hospitalized children. J Nepal Paediatr Soc 2016;36(3):273-276